(untitled) (American Journal of Pedagogical and Educational Research, 2023)
In this article is mentioned examples about putting in force rank of tovachilik based on the historical sources, as such another examples are noted from successful experience of great colonel Sakhibkiran Amir Temur about structure of troops and of gathering troops.